Estudio de prefactibilidad para la instalación de una planta productora de vodka a base de papa amarilla (Solanum phureja) - Castillo Marroquin, Alvaro (2020)
In the present study, all the preliminary aspects of the investigation will be exposed; explaining the research problem, the objectives that come from this and the following chapters will touch essential themes for the implementation of this project, which estimates a useful life of 5 years. The first chapter presents a general framework of ideas, objectives, scope, rationale and the hypothesis of the present work. In the second chapter a whole market study is developed, which is relevant to determine the possible market available to introduce the product and everything related to marketing and analysis and raw material costs. In the third- and fourth-chapter deals with the plant, its location and size. Different places are evaluated in order to find the ideal one to be able to raise the infrastructure where the productive line will be installed and the different possibilities (market, resources, technology and break-even point) are evaluated in order to have the capacity of production and the optimal size plant. Chapter five develops project engineering. The product is defined, the technologies for the production process, the equipment that is required along with its capacities, the study of environmental impact, occupational safety and health and finally the production program and all that is derived from this. Chapter six studies the organization and administration of the company. All the administrative positions required for the analysis and production processes to be carried out in an optimal way. Finally, in chapter seven, all the budgets are calculated and explained in detail and an economic - financial evaluation of the project is made. It is in the evaluation where the financial NPV of S/ 629,776.51 and a financial IRR of 32.15% is determined and with which it concludes that the project is viable.